Despicable me [videorecording (DVD)] - Pablos, Sergio (Universal Studios Home Entertainment, 2010)
Gru delights in all things wicked. Surrounded by an army of tireless little yellow minions, and armed with his arsenal of shrink rays, freeze rays, and battle-ready vehicles for land and air, he vanquishes all who stand in his way. Until the day he encounters the immense will of three little orphaned girls who look at him and see something that no one else has ever seen: a potential dad.